Review of Islamic Economic Law on Islamic Banking Service Contracts - Muhamad Maulana Darsono; Mohamad Anton Athoillah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Financial service activities provided by Islamic banking in Indonesia are applied with various service contracts such as wakalah, hawalah and kafalah. In its current operation, the service contract is still an issue that is discussed, especially regarding the suitability of the contract for sharia requirements. The purpose of this research is to analyze the service contracts of Islamic banks in the review of fiqh muamalah maliyah. The type of qualitative research used in this research describes descriptively to share a clear reflection of the application of contracts used in service products provided by Islamic banks. Literature research in this research is attempted by collecting data both in the form of a novel diary of Fatwa DSN, KHES to strengthen the conclusion. The results of this research describe the operational concepts of service contracts: wakalah, hawalah and kafalah in Islamic banking. Furthermore, the findings in this research state that the service contracts on wakalah, hawalah and kafalah contracts applied to various products in Islamic banking are suitable in the review of fiqh muamalah maliyah.